Visual Functioning and Its Relations With Quality of Life in the Older People Using Governmental Outpatient Clinics Services in the City of Boushehr - Mohammad Mohammadiannia; Mahshid Foroughan; Mehdi Rassafiani; Samaneh hosseinzadeh (University of Social Welfare & Rehabilitation Sciences, 2013)
Objectives: Visual impairment is among the ten most prevalent conditions leading to disability. More than 2/3 of adults who suffer from visual problems are at ages of 65 years and over. The aim of this research was to determine the relation between visual functioning and quality of life in elderly who receive health services at the governmental out-patient clinics of the City of Boushehr. Methods & Materials: The present research is a descriptive analytical study which was implemented by cross-sectional method. The random cluster sampling was used. Two questionnaires consisting of visual function questionnaire (VFQ-25) and short form (SF-36) were used for collecting data. Gathered data were analyzed using correlation coefficient of Spearman, Mann-Whitney and Kruskal-Wallis tests. Results: Gathered data from 173 participants analyzed. The mean age of study subject was 69.3±6.8 years, and 71.1% were male. Results showed that visual functioning (67.82±17.24) and quality of life (56.41±23.29) of the participants were at the intermediate level and there was a direct and significant relation between visual functioning and quality of life of the participants (P≤0.0001). This relation stood in spite of the varying age, sex and educational levels. Advanced age, not having a spouse, and illiteracy enhanced the correlation of visual functioning with quality of life. Conclusion: Delivering preventive, screening, visual treatment along with its rehabilitation services in elderly, especially to the mentioned at risk groups, are recommended.